Toxicological Implications and Inflammatory Response in Human Lymphocytes Challenged with Oxytetracycline. Issue 4 (5th November 2015) - Di Cerbo, A.; Palatucci, A. T.; Rubino, V.; Centenaro, S.; Giovazzino, A.; Fraccaroli, E.; Cortese, L.; Ruggiero, G.; Guidetti, G.; Canello, S.; Terrazzano, G.
ABSTRACT: Antibiotics are widely used in zoo technical and veterinary practices as feed supplementation to ensure wellness of farmed animals and livestock. Several evidences have been suggesting both the toxic role for tetracyclines, particularly for oxytetracycline (OTC). This potential toxicity appears of great relevance for human nutrition and for domestic animals. This study aimed to extend the evaluation of such toxicity. The biologic impact of the drug was assessed by evaluating the proinflammatory effect of OTC and their bone residues on cytokine secretion by in vitro human peripheral blood lymphocytes. Our results showed that both OTC and OTC‐bone residues significantly induced the T lymphocyte and non‐T cell secretion of interferon (IFN)‐γ, as cytokine involved in inflammatory responses in humans as well as in animals. These results may suggest a possible implication for new potential human and animal health risks depending on the entry of tetracyclines in the food‐processing chain.